Estudo fitoquímico e bioatividade de extratos de casearia javitensis kunth. - (:unkn) unknown (Universidade Federal do Amazonas, 2010)
The objective of the present study was to evaluate the antimicrobial, antioxidant and cytotoxicity potentials of extracts of leaves and branches of Casearia javitensis, and to purify and identify their secondary metabolites. Leaves and branches were collected in Reserva Adolpho Ducke, Manaus, AM. The plant material was dried, grinded and the extracts were prepared with DCM, MeOH and water using ultrasound for 20 minutes each. The extracts were concentrated and tested for antibacterial, cytotoxicity and antioxidant activity. Antibacterial activity assays were done using the agar diffusion method by well technique, against Aeromonas hydrophila, Staphylococcus aureus, Escherichia coli and Pseudomonas aeruginosa. Minimum inhibitory concentration (MIC) and the minimum bactericidal concentration (MBC) were measured for the most active extracts. The cytotoxicity assay employed brine shrimp Artemia salina and the evaluation of antioxidant activity used a method with DPPH and ascorbic acid. DCM branches extract was fractioned in chromatographic column (CC), and recrystallization. Gas Chromatography-Mass Spectrometry (GC-MS) and Nuclear Magnetic Resonance (NMR) analyses afforded steroids, as β-sitosterol. DCM extracts of leaves and branches were analyzed by GC-MS in appropriated conditions to steroids and triterpenes analyses, and triterpene friedelin was detected in branches extracts. Antimicrobial assay showed high activity for branches MeOH extract and leaves MeOH extract against A. hydrophila, MIC value < 2 mg/mL and showed no cytotoxicity in Artemia salina. These MeOH extracts were dissolved in water and partitioned between dichloromethane (DCM), ethyl acetate (AcOEt) and n-buthanol (n-BuOH), and these phases were tested for antibacterial activity. The AcOEt phases were the most active, and showed high antimicrobial activity. The DCM phase from branches MeOH extract was fractioned by CC and afforded β-friedelanol. The AcOEt fraction of branches MeOH extract was fractioned by CC and some fractions were purified by HPLC, and afforded five phenolic glycosides, which structures are not yet determined. 1D and 2D-NMR and mass spectrometry analyses are still on progress. The n BuOH phase from branches MeOH extract was fractioned by exclusion chromatography (Sephadex LH-20) and subjected to CC over a Poliamide-6 column, and NMR analyses of one fraction suggest the presence of a phenolic glycoside.
Keywords: Alicaceae; Atividade antimicrobiana; Cromatografia; Fenólicos glicosilados; Salicaceae; Antimicrobial activity; Chromatography; Phenolic glycoside; CIÊNCIAS BIOLÓGICAS